2014
DOI: 10.1089/acm.2013.0122
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Far-Infrared Irradiation on Myofascial Neck Pain: A Randomized, Double-Blind, Placebo-Controlled Pilot Study

Abstract: Short-term treatment using the cFIR neck device partly reduced muscle stiffness. Although the differences in the VAS and PPT scores for the experimental and control groups were not statistically significant, the improvement in muscle stiffness in the experimental group warrants further investigation of the long-term effects of cFIR treatment for pain management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 46 publications
2
44
0
Order By: Relevance
“…Furthermore, Wong et al [41] showed that 15 minutes of FIR exposure per day for five consecutive days was able to diminish subjective pain sensation and decrease serum interleukin-6 and endothelin-1 concentrations (which are biomarkers of pain) in subjects following total knee arthroplasty. On the other hand, a randomized double-blinded placebo clinical study observed that a neck device containing FIR ceramic particles incorporated into fibres was not more effective than a placebo device in decreasing chronic neck and shoulder muscle pain, after one week of daily treatment [42]. Hausswirth et al [17] performed a running protocol to induce muscle damage in runners and applied FIR (lamps) immediately after and 24 h and 48 h after exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Wong et al [41] showed that 15 minutes of FIR exposure per day for five consecutive days was able to diminish subjective pain sensation and decrease serum interleukin-6 and endothelin-1 concentrations (which are biomarkers of pain) in subjects following total knee arthroplasty. On the other hand, a randomized double-blinded placebo clinical study observed that a neck device containing FIR ceramic particles incorporated into fibres was not more effective than a placebo device in decreasing chronic neck and shoulder muscle pain, after one week of daily treatment [42]. Hausswirth et al [17] performed a running protocol to induce muscle damage in runners and applied FIR (lamps) immediately after and 24 h and 48 h after exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, by increase local temperature of operating hands could associate with increase microcirculation to against muscular weakness and soreness, especially to the wrist joint. According to our previous human trial by application of BIOCERAMIC necklace, was found successfully to reduce muscle stiffness of neck, which was assessed of severity of pain by using Visual Analogue Scale (VAS) and Pressure-Pain Threshold (PPT) [31]. To explain the results of these two human studies, future investigations on the effects of BIOCERAMIC on inflammatory pain or inflammatory arthritis should be more concentrated on the biomolecular level.…”
Section: Discussionmentioning
confidence: 99%
“…Since excess stimulation sympathetic nervous system activity is associated with hyperglycemia. PLB enhanced parasympathetic nervous system and counteract sympathetic nervous system activity, suppose to help ameliorate hyperglycemia [22][23][24] Table 2: Hypothesis and mechanism of PLB's effect on hyperglycemia.…”
Section: Molecular Diffusionmentioning
confidence: 99%
“…According to a series of our human trials by application of BIOCERAMIC material made, we found reduced muscle stiffness of neck as well as musculoskeletal disorders from extended use of computers and overwork. PLB has a tendency to stimulate parasympathetic responses, which may reduce pain of dysmenorrhea, resting energy expenditure and improve cardiorespiratory recovery following exercise, as well as induce flowwave effect on acupuncture points through meridians [22][23][24][25][26]. This study presents a series of physical-biological experiments on the material based on its characteristics of biological effects of electromagnetic non-ionizing radiation [27], nonlinear photonic crystal [28], and photoluminescence [29,30].…”
Section: Introductionmentioning
confidence: 99%